Corticosteroid dosing and opioid use are high in patients with SLE and remain elevated after belimumab initiation: a retrospective claims database analysis - Karen H Costenbader; Jianmin Wu; Julie A Birt; Kirstin Griffing; Natalia Bello; Nicole Princic; Isabelle Winer; Carolyn R Lew (Lupus Science and Medicine)
Objectives To investigate corticosteroid and opioid use among patients with SLE and to examine the impact of belimumab initiation on the use of other SLE therapies.Methods We identified adult patients with SLE (International Classification of Diseases, 9th Revision/10th Revision 710.0 and M32) between 1 January 2012 and 31 May 2018 (earliest SLE diagnosis=index date) within MarketScan administrative claims data. Patients were followed from index date for a minimum of 12 months and until the earlier of disenrolment in their health plan or study end (31 May 2018). Corticosteroid utilisation, corticosteroid dose (in prednisone equivalents) and opioid utilisation (overall, by strength (weak, strong) and by duration (chronic use defined as >90 days of cumulative drug supply)) were measured during follow-up. Oral corticosteroid and opioid use were compared in the 6 months before and after initiation of belimumab.Results There were 49 413 patients with SLE eligible for analysis (mean (SD) age: 50.1 (14.0) years, 90.2% female). Of these, 68.5% received corticosteroids, and the average number of prescriptions was 4.59 (4.11) over the first 12 months of follow-up. Among patients with oral corticosteroids, average daily dose was 19.4 (14.2) mg and 59.6% had an average daily dose of ≥15 mg. Half (52.6%) had at least one opioid prescription and of these, 34.6% had chronic use over the first 12 months of follow-up. Among patients initiating belimumab during follow-up (n=1710), oral corticosteroid use decreased by 9.1% (p=0.001), and average daily dose decreased from 14.5 (18.4) mg to 11.9 (18.0) mg (p<0.001) in the 6 months after initiation compared with the 6 months prior. Initiation of belimumab had no impact on prevalence of opioid use.Conclusions A high proportion of patients with SLE are treated with corticosteroids to control SLE and opioid therapy to manage chronic pain. While there was no change in opioid use, oral corticosteroid use and dose intensity decreased following initiation of belimumab.